A relação entre a responsabilidade na gestão fiscal e a qualidade da educação nos municípios mais populosos do Brasil - Costa, Francisco Hedson da (Brasil, 2017)
The Federal Constitution of 1988 transferred to municipal governments responsibility for provision a significant portion of public services, especially educational services related to elementary education. With the approval of the Fiscal Responsibility Law, a new standard in fiscal management was established in the Brazilian Public Sector of the Country, including in the municipal scope. The objective of this work is to investigate the relationship between the responsibility in municipal fiscal management and the quality of education of municipal teaching systems, using as proxies the Fiscal Management FIRJAN Index (IFGF) and the Basic Education Development Index (IDEB), respectively. To achieve the proposed goal, a quantitative methodological approach was used, through a regression with panel data, comprising 227 Brazilian municipalities (with a population of more than 100 000 inhabitants), and used data from 2006 to 2015. The statistical model considers as the dependent variable the IDEB for the initial years of elementary education and as independent variables the five indicators that make up the IFGF. In addition to these indicators, the model used as control variables the percentage of taxes and transfers linked to education applied in expenses with Maintenance and Development of Teaching (MDE), as well as two qualitative variables to capture the regional effects on the educational result of the municipal entity. The results of the research present indications as to the existence relationship between the responsibility in fiscal management and the quality of education, since the fiscal management variables related to the generation of own revenue and to the cost of debt are positively related to the results of the IDEB for the initial years. The indicators related to personnel expenditure, investments expenditure and financial liquidity, together with the indicator of application in expenses with MDE, are statistically null and have no explanatory power on the results of municipalities in said educational indicator. Finally, the qualitative variables of regional location also reveal statistical significance in the results of the IDEB for the initial years, evidencing a positive relation with the municipalities located in the South and Southeast regions of Brazil. On the other hand, for the municipalities belonging to the North and Northeast regions, the results indicate a negative relation with the indicator of educational quality observed by the education systems of municipalities with population of more than 100 000 inhabitants.
Keywords: Gestão fiscal; Educação; Municípios; CNPQ::CIENCIAS SOCIAIS APLICADAS: CIÊNCIAS CONTÁBEIS